YOUTH UNEMPLOYMENT IN GUJARAT: A SOCIO-LEGAL STUDY OF EDUCATED UNEMPLOYED YOUTH AND POLICY IMPLICATIONS - Rizwani Pinky Ashokkumar; Dr. Udey Desh Pandey (International Educational Journal of Science and Engineering, 2025)
Youth unemployment, particularly among educated individuals, has emerged as a critical socio-legal issue in Gujarat. This research paper examines the underlying causes, socio-economic consequences, and legal frameworks addressing youth unemployment in the state. It analyzes employment policies, skill development initiatives, and legal protections, offering insights into their effectiveness. Through empirical and doctrinal analysis, the study identifies key gaps and suggests policy reforms to enhance youth employability and economic participation.Youth unemployment, particularly among educated individuals, is a growing socio-legal challenge in Gujarat. Despite the state’s economic progress, a significant number of graduates and postgraduates struggle to secure suitable employment, leading to social and economic instability. This research paper examines the causes of educated youth unemployment, including skill mismatches, limited industrial absorption, and policy gaps. It critically analyzes the legal and policy frameworks governing employment in Gujarat, assessing the effectiveness of government initiatives such as skill development programs and employment schemes. By conducting a socio-legal analysis, the study identifies key challenges in policy implementation and proposes reforms, including stronger industry-academia collaboration, improved vocational training, and targeted legal measures to enhance employability. Comparative insights from other Indian states and international models highlight best practices that could be adapted to Gujarat’s context. The paper concludes with policy recommendations to bridge the education-employment gap and promote sustainable job opportunities for educated youth.